Tricontrollable pixelated metasurface for absorbing terahertz radiation - Kumar P.; Lakhtakia A.; Jain P.K. (My University, 2025)
The incorporation of materials with controllable electromagnetic constitutive parameters allows the conceptualization and realization of controllable metasurfaces. With the aim of formulating and investigating a tricontrollable metasurface for efficiently absorbing terahertz radiation, we adopted a pixel-based approach in which the meta-atoms are biperiodic assemblies of discrete pixels. We patched some pixels with indium antimonide (InSb) and some with graphene, leaving the others unpatched. The bottom of each meta-atom was taken to comprise a metal-backed substrate of silicon nitride. The InSb-patched pixels facilitate the thermal and magnetic control modalities, whereas the graphene-patched pixels facilitate the electrical control modality. With proper configuration of patched and unpatched pixels, and with proper selection of the patching material for each patched pixel, the absorptance spectra of the pixelated metasurface were found to contain peak-shaped features with maximum absorptance exceeding 0.95, full-width-at-half-maximum bandwidth of less than 0.7 THz, and maximum-absorptance frequency lying between 2 THz and 4 THz. The location of the maximum-absorptance frequency can be thermally, magnetically, and electrically controllable. The lack of rotational invariance of the optimal meta-atom adds mechanical rotation as the fourth control modality. © 2019 Optical Society of America.